2006
DOI: 10.1103/physreve.73.041930
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-dependent capacitance of human embryonic kidney cells

Abstract: We determine membrane capacitance, C as a function of dc voltage for the human embryonic kidney (HEK) cell. C was calculated from the admittance, Y, obtained during a voltage ramp when the HEK cell was held in whole-cell patch-clamp configuration. Y was determined at frequencies of 390.625 and 781.25 Hz from the measured current, i obtained with a dual-sinusoidal stimulus. We find that the fractional increase in the capacitance, C is small (<1%) and grows with the square of the voltage, Ψ. C can be described b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 78 publications
(90 reference statements)
4
38
0
Order By: Relevance
“…For the simulated systems with NaCl, only 60mM salicylate caused a significant increase (p < 0.05) in the electrostatic potential at the water-lipid interface. This increase is in qualitative agreement with experiments demonstrating salicylate-induced changes in membrane potentials (17,72) and surface charges (15) for human embryonic kidney (HEK) cells as well as various types of neurons (73)(74)(75)(76).…”
Section: Electrostatic Potential and Dielectric Propertiessupporting
confidence: 89%
See 1 more Smart Citation
“…For the simulated systems with NaCl, only 60mM salicylate caused a significant increase (p < 0.05) in the electrostatic potential at the water-lipid interface. This increase is in qualitative agreement with experiments demonstrating salicylate-induced changes in membrane potentials (17,72) and surface charges (15) for human embryonic kidney (HEK) cells as well as various types of neurons (73)(74)(75)(76).…”
Section: Electrostatic Potential and Dielectric Propertiessupporting
confidence: 89%
“…OHCs play an important role in the sensitivity of mammalian hearing for high-frequency sounds through a mechanism of electromechanical feedback (12). While the exact molecular mechanism of salicylate's effect on OHC electromechanical response is still unknown, experimental work has suggested that salicylate may interact with several components of the OHC, including the phospholipid bilayer (13)(14)(15)(16)(17)(18)(19)(20) and membrane-bound proteins such as prestin (21)(22)(23). In this study, we have investigated one aspect of salicylate's effects on OHC electromechanical coupling: the perturbation of electrical and mechanical biomembrane properties by salicylate in the absence cytoskeletal components or membrane-bound motor proteins such as prestin.…”
mentioning
confidence: 99%
“…Further experiments include the measurements of the currents in voltage-clamped configuration. Membrane capacitance of DRG neurons is 12 pF [36] while it is 26 pF for C elegans [17], 200 nF for oocyte [37] and 7 to 8 pF for HEK [38]. Since membrane capacitances from DRG neurons and HEK cells are similar, it is unlikely that this parameter alone is the key value for the decrease of dT/dt observed in our work.…”
Section: Discussionmentioning
confidence: 43%
“…Electrophysiological data were obtained from cells using the whole-cell voltage-clamp technique. Our recording techniques are fully described previously (Farrell et al, 2006); a brief description follows. Culture dishes containing transfected cells were placed on the stage of an inverted microscope (Zeiss, Gottingen, Germany).…”
Section: Methodsmentioning
confidence: 99%